2018
DOI: 10.1016/j.redox.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Iron-loaded transferrin (Tf) is detrimental whereas iron-free Tf confers protection against brain ischemia by modifying blood Tf saturation and subsequent neuronal damage

Abstract: Despite transferrin being the main circulating carrier of iron in body fluids, and iron overload conditions being known to worsen stroke outcome through reactive oxygen species (ROS)-induced damage, the contribution of blood transferrin saturation (TSAT) to stroke brain damage is unknown. The objective of this study was to obtain evidence on whether TSAT determines the impact of experimental ischemic stroke on brain damage and whether iron-free transferrin (apotransferrin, ATf)-induced reduction of TSAT is neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 56 publications
7
63
0
Order By: Relevance
“…In MCAO animals, the iron intake was positively associated with the infarct volume ( Castellanos et al, 2002 ; García-Yébenes et al, 2012 ). Consistently, one in vitro study demonstrated that holo-transferrin increased ROS production, and caused neuronal cell death induced by deprivation of oxygen and glucose ( DeGregorio-Rocasolano et al, 2018 ). The experimental results also illustrated that administration of exogenous apotransferrin reduced brain damage and improved neurological outcomes with decreased lipid peroxidation, supporting the involvement of ferroptosis in ischemia ( DeGregorio-Rocasolano et al, 2018 ).…”
Section: The Role and Mechanism Of Ferroptosis In Acute Cns Injuriesmentioning
confidence: 76%
See 1 more Smart Citation
“…In MCAO animals, the iron intake was positively associated with the infarct volume ( Castellanos et al, 2002 ; García-Yébenes et al, 2012 ). Consistently, one in vitro study demonstrated that holo-transferrin increased ROS production, and caused neuronal cell death induced by deprivation of oxygen and glucose ( DeGregorio-Rocasolano et al, 2018 ). The experimental results also illustrated that administration of exogenous apotransferrin reduced brain damage and improved neurological outcomes with decreased lipid peroxidation, supporting the involvement of ferroptosis in ischemia ( DeGregorio-Rocasolano et al, 2018 ).…”
Section: The Role and Mechanism Of Ferroptosis In Acute Cns Injuriesmentioning
confidence: 76%
“…Consistently, one in vitro study demonstrated that holo-transferrin increased ROS production, and caused neuronal cell death induced by deprivation of oxygen and glucose ( DeGregorio-Rocasolano et al, 2018 ). The experimental results also illustrated that administration of exogenous apotransferrin reduced brain damage and improved neurological outcomes with decreased lipid peroxidation, supporting the involvement of ferroptosis in ischemia ( DeGregorio-Rocasolano et al, 2018 ). What’s more, the iron levels in the brain increased as humans age ( Ward et al, 2014 ), which may exacerbate ischemic stroke.…”
Section: The Role and Mechanism Of Ferroptosis In Acute Cns Injuriesmentioning
confidence: 76%
“…However, more than one-half of patients fail to demonstrate clinical improvement (Yeo et al, 2013;Kikuchi et al, 2014). An increasing number of recent studies confirmed that free iron accumulates in the ipsilateral hypoxic-ischemic neonatal rat cortex (Palmer et al, 1999), total iron is increased significantly in the ischemic areas after ischemic stroke (Tuo et al, 2017), and the levels of transferrin receptors (TfRs) and iron-loaded transferrin (holo-transferrin, HTf) also increase after ischemic stroke (Park et al, 2011;DeGregorio-Rocasolano et al, 2018). All of this evidence indicates that a new cell death mechanism may play a very important role in EBI after ischemic stroke: ferroptosis (Dixon et al, 2012;Alim et al, 2019;Guan et al, 2019;Datta et al, 2020).…”
Section: Ischemic Strokementioning
confidence: 99%
“…In the cytosol, unused iron is stored into FT, a molecule composed of 24 subunits of a variable proportion of heavy and light chains, that shields up to 4500 iron atoms in a redox inert state. Neurons express both TfR1 and DMT1 (Pelizzoni et al, 2012; DeGregorio-Rocasolano et al, 2018); DMT1 is mainly found in the cytoplasm colocalizing with endosomes/lysosomes. Further, neurons express the iron export molecule FPN (Burdo et al, 2001; Zhou et al, 2017).…”
Section: Iron Uptake and Handling By Parenchymal Brain Cellsmentioning
confidence: 99%